THE CONCEPT OF THE COOPERATIVE-LOCAL MICRO-NETWORK AS AN INSTRUMENT OF INCLUSIVE DEVELOPMENT AND SUPPORT OF UKRAINE'S ENERGY SECURITY - LYPOV, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the prerequisites and presents the motivational grounds and concepts of creating digital platform cooperatives (DPs) as the basis for the formation of local microgrids of renewable energy generation (LMREG). The cooperation of small local RES producers, "Platform Cooperativeism", is considered as a tool of inclusive development, an alternative to "Platform Capitalism" as a result of the monopolization of markets by platforms - digital intermediaries.An overview of research on the development of cooperation of small REG producers is presented. The reasons hindering its development in Ukraine have been revealed. Attention is focused on the potential advantages that can be created by the use of the cross-subsidization effect inherent in the DP for the development of LMREG based on DP cooperatives. The structural and functional scheme of the cooperative DP of LMREG is proposed. Its structural components include the CPU core, the local self-government body, groups of legal entities and individuals - prosumers, who combine the roles of producers and consumers of electricity, as well as investors who invest in the development of the cooperative but do not have their power-generating equipment. The functional component provides generation, accumulation, and distribution of energy flows, their monitoring, data accumulation and analysis, algorithmic control and balancing of the state of the microgrid, provision of data for mutual calculations between its participants, and interaction with the unified energy system of Ukraine. The motivational reasons for participation in the Cooperative-DP of various groups of power generation equipment owners are analyzed. The possible consequences of the formation of the DP core - LMREG on a commercial basis are characterized.
Keywords: energy; security; cooperatives; digital platforms; inclusive development; platform capitalism; renewable energy